Prevalence of sexual dysfunction and impact of contraception in female German medical students - Wallwiener, Christian Wilhelm; Wallwiener, Lisa-Maria; Seeger, Harald Michael; Mueck, Alfred O.; Bitzer, Johannes; Wallwiener, Markus (The journal of sexual medicine, 2010)
Female sexual dysfunction (FSD) is a very common disorder, with an estimated prevalence of having at least one sexual dysfunction of about 40%. - Aim - To investigate the prevalence and types of FSD and the relationship between hormonal contraception (HC) and FSD in female German medical students. - Main Outcome Measures - Female Sexual Function Index (FSFI) with additional questions on contraception, sexual activity, and other factors that may influence sexual function.
Gesehen am 28.09.2023